2020
DOI: 10.1186/s12864-020-6656-3
|View full text |Cite
|
Sign up to set email alerts
|

Genome‑wide integrated analysis demonstrates widespread functions of lncRNAs in mammary gland development and lactation in dairy goats

Abstract: Background: The mammary gland is a unique organ for milk synthesis, secretion and storage, and it undergoes cyclical processes of development, differentiation, lactation and degeneration. At different developmental periods, the biological processes governing mammary gland physiology and internal environmental homeostasis depend on a complex network of genes and regulatory factors. Emerging evidence indicates that lncRNAs have arbitrarily critical functions in regulating gene expression in many organisms; howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 45 publications
1
13
1
Order By: Relevance
“…These were less than those reported in mammary gland tissue of dairy goats, with an average of 2381 predicted lncRNAs [18]. This likely reflects species-specific expression patterns, and the species-specific expression has been observed in the mammary gland of dairy cows and dairy goats [16,18]. Most lncRNAs identified in the study were expressed at low levels in the ovine mammary gland.…”
Section: Discussioncontrasting
confidence: 60%
See 3 more Smart Citations
“…These were less than those reported in mammary gland tissue of dairy goats, with an average of 2381 predicted lncRNAs [18]. This likely reflects species-specific expression patterns, and the species-specific expression has been observed in the mammary gland of dairy cows and dairy goats [16,18]. Most lncRNAs identified in the study were expressed at low levels in the ovine mammary gland.…”
Section: Discussioncontrasting
confidence: 60%
“…In the study, a total of 1770 and 1742 lncRNAs were found in mammary gland of lactating GAM and STH ewes, respectively. These were less than those reported in mammary gland tissue of dairy goats, with an average of 2381 predicted lncRNAs [18]. This likely reflects species-specific expression patterns, and the species-specific expression has been observed in the mammary gland of dairy cows and dairy goats [16,18].…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…For example, Ma et al (2018) profiled mRNA and lncRNA expression in sheep that differed in the deposition of fat in their tails and identified several DE mRNAs and lncRNAs, suggesting that they may play crucial roles in the deposition of tail fat. Ji et al (2020) characterized the mRNA and lncRNA expression profiles in dairy goats from different lactation periods and found that the expression of lncRNAs was tied to mammary gland development and lactation. However, little comparative research of the lncRNAs and mRNAs in sheep lactation has been conducted.…”
Section: Introductionmentioning
confidence: 99%